Description of three new species of biting midge of the genus Atrichopogon Kieffer (Diptera: Ceratopogonidae) from Brazilian Amazon - de Sousa Farias, Emanuelle; Santos, Sanmya Silva Dos; Paulino-Rosa, Jokebede Melynda Dos Santos; Pessoa, Felipe Arley Costa (Zootaxa, 2021)
Three new species of Atrichopogon with spotted wings of the family Ceratopogonidae (Diptera: Culicomorpha) from the Amazonas State of Brazil are described and illustrated. Male and female specimens of Atrichopogon janseni sp. nov., A. riopardensis sp. nov., and A. sergioluzi sp. nov. were associated by wing pigmentation patterns: with two darker spots, one over r-m and the other one in cell r3, posterior to the apex of R3. Male A. janseni sp. nov. have tergite 9 that is 2.5 × as broad as long, not extending to the apex of gonocoxite, and sternite 9 stout, sub-trapezoidal, with distal margin with a row of stout spines; gonostylus of A. janseni sp. nov. is spatulate, with distinct middle notch. Atrichopogon riopardensis sp. nov. is separated from other species with similar wing patterns and forked gonostylus, with gonostylus forked near midlength, with longitudinal furrow, inner portion short and fingernail-like, outer portion elongate and apically curved directed mesally; outer portion is 4 × longer than inner, with one long seta in basal 1/3. Contrastingly, A. sergioluzi sp. nov. has a small fork at the apex of gonostylus, and cercus broad basally with rounded tip. Females of the three new species are very similar (as are other females in this group), and it is probably not possible to distinguish them using the morphological features described. With the addition of the three new species described here, there are now known 15 Neotropical species of Atrichopogon with pigmented wings.